Structure–property relationship study of the HPLC enantioselective retention of neuroprotective 7‐[(1‐alkylpiperidin‐3‐yl)methoxy]coumarin derivatives on an amylose‐based chiral stationary phase. Issue 6 (30th March 2018) - Pisani, Leonardo; Rullo, Mariagrazia; Catto, Marco; de Candia, Modesto; Carrieri, Antonio; Cellamare, Saverio; Altomare, Cosimo Damiano
Abstract: The enantiomer separation of a number of racemic 7‐[(1‐alkylpiperidin‐3‐yl)methoxy]coumarin derivatives, some of which show outstanding in vitro multitarget neuroprotective activities, was successfully achieved on a polysaccharide‐based chiral stationary phase, bearing amylose tris(3, 5‐dimethylphenylcarbamate) as a chiral selector, in normal polar mode (methanol and acetonitrile as the mobile phases). The majority of the screened selectands, especially those bearing 1‐(3‐X‐benzyl)piperidin‐3‐yl moieties, showed baseline enantiomer separations, and compound8 (X = NO2 ) was the best resolved ( α  = 2.01; R S  = 4.27). Linear free energy relationships, usefully complemented by molecular docking calculations, have the key role in enantioselective retention of aromatic interactions between π‐donor moieties in the chiral selector and π‐acceptor moieties in selectand, strengthened by hydrogen bond interaction between a hydrogen bond donor in the chiral selector and the hydrogen bond acceptor group(s) in the selectand. Statistically, reliable equations highlighted the importance of the substituent's size and substitution pattern ( meta better than para ) to affect the enantiorecognition of the title compounds. The chromatographic data support the scalability of the optimized experimental conditions for preparative purposes.